Empirical investigation of three selected self-disclosure measures, and some theoretical and methodological considerations for self-disclosure research - Pors, Johannes (Department of Psychology, 2015)
An analysis of theoretical trends in research on self-disclosure lends support to Benner's (1968) distinction between cognitive, behavioural and affective dimensions to the self-disclosure construct. However, since there is very little attempt in the research at coordinating theoretical and practical (measurement) aspects (the importance of which is stressed by Fiske & Pearson, 1970), problems have arisen, the most serious of which is the fact that the test constructors in this field always assume their instruments to measure the totality of the target concept. On the basis of the above three-dimensional view, a logical assumption was made that of the twenty-three different types of self-disclosure measures to date, three measures appear to be emphasizing one aspect of self-disclosure, i.e. the affective dimension, viz.: an Essay Topic procedure after Burhenne & Mirels (1969) stressing affect by virtue of the rating procedure; the Hurley Rating Scale (1968), stressing affect by means of its introductory and definitive paragraphs; and the Shapiro Disclosure Seale (1969) consisting of statements referring to behaviours with positive or negative affect. One would expect these measures to correlate positively as they are all measures of 'self-disclosure'. Since the three chosen measures in addition specifically stress the affective dimension of the construct it was hypothesized that they would correlate strongly.